Neuroimmunology: An Expanding Frontier in Autoimmunity - Höftberger, Romana (Frontiers in Immunology, 2015)
Anti-neuronal autoimmune encephalitis (AIE) comprises a recently characterized group of immune-mediated disorders that result in limbic, multifocal, or diffuse encephalitis due to direct interaction of autoantibodies with neuronal surface or synaptic proteins. The pathological effects of the autoantibodies vary according to the target antigen but when they are removed neuronal dysfunction is commonly reversed. Ongoing research on AIE constantly increases the number of novel autoantibodies and expands the spectrum of neurological syndromes that are important in the differential diagnosis of psychiatric illness, dementia, or viral encephalitis. This review summarizes recent advances in AIE, focusing on pathogenetic mechanisms and novel associations with other CNS disorders such as neurodegeneration, relapsing symptoms post-herpes simplex virus encephalitis, and demyelinating diseases. In addition, an algorithmic approach to detect and characterize neuronal cell surface autoantibodies is proposed.